Fifth Five Year Plan Uttar Pradesh Draft Annual Plan 1976-77 Vol. I - Planning Commission (Planning Commission, 1976)
The economic outlook as a result of partial recovery during the later-half of 1974-75 has brightened up as compared to the previous year. According to quick estimates the total State income, a barometer for measuring the health of the economy, stood at nearly Rs.7,500 crores at current prices during 1971-75. which was about 11 percent higher than the income of 1973-71 at the prices of that year. In real terms it meant, an increase of about 3.5 per cent if the effect of price-rise is removed.
Planning Department, Uttar Pradesh